2013
DOI: 10.1016/j.jpedsurg.2012.09.067
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile polyposis of infancy in a child with deletion of BMPR1A and PTEN genes: Surgical approach

Abstract: Juvenile polyposis of infancy is the most severe and life-threatening form of juvenile polyposis. This disease typically presents in the first two years of life with gastrointestinal bleeding, diarrhea, inanition, and exudative enteropathy. In very few reports concerning this entity, a large deletion in the long arm of chromosome 10 (10q23), encompassing the PTEN and BMPR1A genes, was found. The authors report a case of delayed diagnosis of juvenile polyposis of infancy at 6 years of age. A 3.34 Mb long de nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Most patients have either a SMAD4 or BMPR1A loss of function variant. Case studies have also identified a correlation between chromosome 10q23 deletions including BMPR1A and PTEN with rare onset of a spectrum of phenotypically heterogenous polyposis syndromes [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most patients have either a SMAD4 or BMPR1A loss of function variant. Case studies have also identified a correlation between chromosome 10q23 deletions including BMPR1A and PTEN with rare onset of a spectrum of phenotypically heterogenous polyposis syndromes [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile polyposis syndrome (JPS) is a rare autosomal dominant disease associated with hamartomatous growths that can occur throughout the gastrointestinal (GI) tract of affected children [1,2]. Infantile JPS is a more aggressive form that arises during the first year of life, and is thought to be caused by deletion of the PTEN and/or BMPR1A genes [3][4][5]. Without intervention, infantile JPS is often associated with detrimental health sequelae such as protein losing enteropathy (PLE), blood loss, malabsorption, malnutrition, and intussusception.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported by Oliveira et al, 9 patients with JPI are offered subtotal colectomy combined with intraoperative endoscopic removal of polyps as a palliative disease control. It is remarkable that despite multiple polyp resection or even subtotal colectomy, we were unable to obtain a decrease in the magnitude of protein loss.…”
Section: Discussionmentioning
confidence: 99%